Fostering Diversity, Equity, and Inclusivity in the Language Classroom through Choice, Mastery, and Community: A Motivational Approach - Villalobos-Buehner, Maria (Journal of NELTA, 2024)
This paper explores how DEI initiatives and a motivational approach to teaching off er a superb synergy that will assist educators in supporting students’ language learning fairly, regardless of available resources, as long as there are students and an eager educator ready to break barriers. In this paper, we discuss how DEI initiatives not only help us create fair, empowering, and adaptable language learning environments but also how they can support the three most critical motivational needs of our students autonomy, competence, and relatedness, which, according to the self-determination theory, are strong indicators of behavior initiation and continued engagement in language learning beyond our classrooms.